Optimisation of capacity in various 802.11 gaming scenarios. (12th November 2010) - Qi, Hanghang; Malone, David; Botvich, Dmitri
As IEEE 802.11 WLANs are widely deployed and the popularity of computer games continues increasing, real-time multiplayer games are increasingly played over 802.11 networks. In this paper, we consider the issues of games over 802.11 wireless networks and give a framework to study this kind of applications. A multiplayer game traffic model is produced using Quake 4 as an example. By introducing IEEE 802.11 MAC model, we show how the performance changes as the number of players increases including throughout, delay, jitter and Mean Opinion Score (MOS). Several different network scenarios then are considered. The issue of bottleneck effect at the AP is identified and a solution by using 802.11 parameters (TXOP) is given. Validation is made in our testbed and the technique used in this paper could be applied to improve the performance of other real-time applications over 802.11-like networks.